Pemberdayaan Masyarakat Melalui Makanan Sehat Khas Indonesia: Lomba Kreasi dan Workshop Olahan Tempe - Maria Magdalena Wahyuni Inderawati; Anastasia Tatik Hartanti; Herman Yosef Sutarno; Ronald Sukwadi (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2025)
This community service program aims to empower the community by processing healthy Indonesian food, especially tempeh. Tempeh, a traditional food rich in health benefits, has enormous potential to improve the community's economic welfare. This activity at Unika Atma Jaya Campus 3 in BSD involved the Faculty of Technobiology, Tempe Research & Development Centre, and the Kampung Tempe Ciomas Tourism Village group. Activities include 'the Tempe Processed Creation Competition' and workshops on 'Hygienic Tempe Production' and 'Making Tempe Skincare and Body Scrub.' The competition aimed to increase participants' creativity in processing tempeh into various innovative dishes. Meanwhile, the workshop provided participants with practical knowledge on how to process healthy and hygienic tempeh. As a result of this activity, 25 groups participated in the competition, and 54 participants attended the workshop. The results of this activity are an increase in public understanding of the benefits of tempeh and an increase in consumption and sales of tempeh products in the community. Thus, this program not only contributes to public health but also to the improvement of the local economy through the development of innovative tempeh products.